Cyberresearch on the ancient Near East and neighboring regions : case studies on archaeological data, objects, texts, and digital archiving - Bigot Juloux, Vanessa (Digital biblical studies., 2018)
CyberResearch on the Ancient Near East and Neighboring Regions presents case studies on archaeology, objects, texts, and online publishing, digital archiving, and preservation. Edited by Vanessa Bigot Juloux, Amy Rebecca Gansell, and Alessandro Di Ludovico, it emphasizes the significance of the digital humanities to Ancient Near Eastern Studies.